Local birthing services for rural women: Adaptation of a rural New South Wales maternity service. (6th July 2016) - Durst, Michelle; Rolfe, Margaret; Longman, Jo; Robin, Sarah; Dhnaram, Beverley; Mullany, Kathryn; Wright, Ian; Barclay, Lesley
Abstract: Objective: To describe the outcomes of a public hospital maternity unit in rural New South Wales (NSW) following the adaptation of the service from an obstetrician and general practitioner‐obstetrician (GPO)‐led birthing service to a low‐risk midwifery group practice (MGP) model of care with a planned caesarean section service (PCS). Design: A retrospective descriptive study using quantitative methodology. Setting: Maternity unit in a small public hospital in rural New South Wales, Australia. Participants: Data were extracted from the ward‐based birth register for 1172 births at the service between July 2007 and June 2012. Main outcome measures: Birth numbers, maternal characteristics, labour, birthing and neonatal outcomes. Results: There were 750 births over 29 months in GPO and 277 and 145 births over 31 months in MGP and PCS, respectively, totalling 422 births following the change in model of care. The GPO had 553 (73.7%) vaginal births and 197 (26.3%) caesarean section (CS) births (139 planned and 58 unplanned). There were almost universal normal vaginal births in MGP (>99% or 276). For normal vaginal births, more women in MGP had no analgesia (45.3% versus 25.1%) or non‐invasive analgesia (47.9% versus 38.6%) and episiotomy was less common in MGP than GPO (1.9% versus 3.4%). Neonatal outcomes were similar for both groups with no difference between Apgar scores at 5 min, neonatal resuscitations or transfer to high‐level special care nurseries. Conclusion: This study demonstrates how a rural maternity service maintained quality care outcomes for low‐risk women following the adaptation from a GPO to an MGP service.